MRI presentation of hepatocellular carcinoma in non-alcoholic steatohepatitis (NASH). Issue 119 (October 2019) - Al-Sharhan, Fatima; Dohan, Anthony; Barat, Maxime; Feddal, Adlane; Terris, Benoit; Pol, Stanislas; Mallet, Vincent; Soyer, Philippe
Highlights: Nearly half of hepatocellular carcinomas in NASH are smaller than 20 mm. One third of hepatocellular carcinomas in NASH do not display wash-out. Classical diagnostic imaging criteria should be applied with caution to HCC in NASH. Abstract: Purpose: To describe the magnetic resonance imaging (MRI) features of hepatocellular carcinoma (HCC) in patients with non-alcoholic steatohepatitis (NASH). Methods: MRI examinations of 21 patients with HCC and NASH were analyzed by two observers. There were 18 men and 3 women with a mean age of 67.9 ± 10.2 (SD) years (range: 36–85 years). Images were qualitatively and quantitatively analyzed with respect to imaging presentation. Results: HCC presented as a single tumor in 13/21 patients (62%), with a mean longest diameter of 26.9 ± 20.2 (SD) mm (range: 12–88 mm); 17/30 HCC (57%) had a largest diameter <20 mm. A signal drop between in- and out-of-phase T1-weighted MR images was observed in 16/30 HCC nodules (53%). All HCC nodules (30/30; 100%) showed hyperenhancement on arterial phase images and 12/30 HCC nodules (40%) did not show a wash-out on portal or delayed phase images. Encapsulation was observed in 18/30 HCC nodules (60%). MRI findings consistent with liver cirrhosis were present in 16/21 patients (76%). Conclusions: Our results show that 57% of HCC in NASH can present as a lesion smaller than 20 mm and 40% do not display wash-out. These results suggest that classical imaging criteria developed for noninvasive diagnosis of HCC should be applied with caution to HCC in patients with NASH.